A fundamental study of leaching kinetics and mechanisms of molybdenite assisted by mechanical activation. (15th January 2019) - Li, Yubiao; Li, Zhiming; Wang, Bing; Dong, Zhaomin; Song, Shaoxian
Graphical abstract: Highlights: Grinding MoS2 significantly increased Mo leaching rate from <2% to >58%. MoS2 ground with Na2 CO3 and NaClO2 produced soluble Na2 MoO4 via solid state reaction. Leaching of co-ground MoS2 and Na2 CO3 and NaClO2 followed two steps. Na2 MoO4 was dissolved within 0.0625 h while ground MoS2 was leached slowly later. Abstract: The mechanical activation was applied as a pre-treatment method to improve molybdenite (MoS2 ) leaching. The effects of grinding ball size, ball to powder mass ratio, milling speed and time, molar ratio of mineral to oxidants, as well as the influence of solution pH, temperature and leaching time were investigated in detail. The results showed an extremely low Mo extraction (less than 2% at acidic and neutral conditions) for MoS2 activated alone. However, Mo extraction was increased significantly after co-grinding of MoS2 with NaClO2 and Na2 CO3, e.g ., more than 58% in any leaching solution applied. Prolonging the grinding time improved Mo extraction but the efficiency was declined gradually, giving rise to an optimum grinding efficiency at 4 h with a molar ratio of 1:3:5 for MoS2 :NaClO2 :Na2 CO3 . Distilled water was selected as the leaching solution since this gave similar Mo recovery to other lixiviants. Higher temperature and longer leaching time were beneficial to Mo extraction. However, it was also found that too large grinding balls and high ball to powder mass ratio adversely affected MoS2 extraction. The kinetics analysis indicated that the leaching of activated MoS2 followed a chemical reaction controlled mechanism. The XRD and SEM analyses indicated that mechanical activation not only reduced the particle size of MoS2 but also triggered solid state reaction to produce soluble Na2 MoO4, thereby improving Mo extraction significantly.